Structural evolution of Ti-Al-Si-N nanocomposite coating - Carvalho, S. (2009)
Ti–Si–Al–N films were prepared by rf reactive magnetron sputtering, in static and rotation modes, using a wide range of different deposition conditions, which created conditions to obtain Ti–Al–Si–N coatings with different structural arrangements. Films prepared below a critical nitrogen flow, under conditions out of thermodynamic equilibrium, revealed a preferential growth of an fcc (Ti,Al,Si)Nx compound with a small N deficiency. With nitrogen flow above that critical value, the reduction of the lattice parameter was no longer detected. However, a thermal annealing showed that a complete thermodynamically driven segregation of the TiN and Si3N4 phases was not yet obtained. The segregation upon annealing induced a self-hardening and showed a multiphase system, where the crystalline TiN, (Ti,Al)N and (Ti,Al,Si)Nx phases were identified by X-ray diffraction. This behavior is due to the de-mixing of the solid solution associated to a small N deficiency.